World Policy Problems in Documents of I Congress of the Communist Internationale - E. N. Yemelyanova (Научный диалог, 2017)
The creation of the Comintern and the formation of the Communist concept of war and peace in the conditions of the Versailles system of international relations are considered. The topic urgency is determined by the fact that the problem of international tensions today is extremely sharp again. The author notes that the search for a new model of world order and a peaceful transition to it makes the appeal to the experience of the past important. The novelty of the research lies in the fact that the coverage of issues of war and peace in the documents of the Comintern in Russian historiography is only beginning to be explored, there have been no fundamental works on this topic yet. The article presents a comparative analysis of democratic and Communist views on the creation of a new system of international relations. Great attention is paid to the work of the I Congress of the Communist Internationale, which laid the foundations of the policies of the international Communist movement. The differences in tactical questions of the Communist Western social democracy, and the differences between “right-wing” and “left-wing” of the Comintern are analyzed. The author comes to the conclusion that, despite the revolutionary rhetoric, the Bolshevik leadership sought to make peace with the great powers and to establish economic relations with them. It is mentioned that the theoretical position of the Communists was adjusted depending on the practical interests of the Soviet state.